PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA BANK MILIK NEGARA (BUMN) YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2007 – 2014 - Ade Syahroni; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of financial ratios againt stock price at the state-owned bank (SOE) that are listed in the Indonesia Stock Exchange (IDX) study period of 2007 - 2014. Financial ratios that use as independent variables is Loan to Deposit Ratio (LDR), Primary Ratio (PR), Return on Assets (ROA), and Net Profit Margin (NPM). While that is used as the dependent variable is the price of shares in state-owned banks (SOE) that are listed in the Indonesia Stock Exchange (IDX). The method used to observe the effect of financial ratios on stock prices is by using multiple linear regression.Data used in this research is secondary data, financial reports (annual report) and performance summary. As for the data bank listed on the Stock Exchange for 8 years from 2007 to 2014. Sampling was done by purposive sampling, as for the sample is 4 state owned banks (SOE). Classic assumption test in this study include normality test, multikoliniearitas, heterocedasticity test, autocorrelation test. Analysis data using multiple linear regression analysis, t test, f test, and coefficient of determination test. Analysis data using multiple linear regression analysis with SPSS 16.The results showed that the LDR, ROA, and NPM variables partially affects significantly againts the price of shares in a bank-owned (SOE) that are listed in the Indonesia Stock Exchange (IDX), while PR variable is not significantly effect the price of bank shares owned by the State (SOE) listed in the Indonesia Stock Exchange (IDX). The results of this research simultaneously (f test) showed a significant effect of the LDR, PR, ROA,and NPM variables againts State-Owned Enterprises stock price (SOE) listed in the Indonesia Stock Exchange (IDX).Keywords: Financial Ratios, Stock Price, LDR, PR, ROA, NPM